Italy's Political Upheaval and the Consequences of Inequality - Mario Pianta (Intereconomics, 2020)
Political upheaval, with the dangerous rise of the far right – in Italy and Europe – is likely to be stabilised when politics and policies again turn their attention to the priorities of the majority of impoverished voters, with a focus on reducing inequalities, unemployment and casualisation.
Keywords: 330